Value Chain Agribisnis Mangga Gedong Gincu (Mangifera Indica l) di Kabupaten Majalengka - Suhaeni, Suhaeni; Karno, Karno; Sumekar, Wulan (AGRARIS: Journal of Agribusiness and Rural Development Research, 2015)
The objective of this research was to analyze the value chain and efficiency of gedong gincu mango agribusiness in Majalengka Regency. The data collection was conducted by interview techniques, using questionnaire. The samples of this study were: 88 farmers gedong gincu mango taken by using proportional random sampling, 28 sellers taken by snowball sampling, consisted of 15 local collectors, 3 big traders and 10 retailers. Value chain was analyzed using R/C ratio. Marketing efficiency was analyzed by calculating the marketing margin, profit margin, farmers share and marketing efficiency. The results showed that R/C ratio of farmers, small collectors, big collectors and retailers were >1. Highest profit level was achieved by farmers. Based on marketing margins, farmers share and marketing efficiency, all marketing channels were categorized as efficient.